Efektivitas Pemberian Jus Wortel dan Air Kelapa Muda Terhadap Perubahan Tekanan Darah Penderita Hipertensi di Polara Raya - Abidan, Nur; Dhesa, Desidarius Bela; Demmalewa, Jenny Qlifianti (Pengurus Daerah Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI) Sulawesi Tenggara, 2024)
Hypertension is a condition of high blood pressure that exceeds 140/90 mmHg. One effort to control hypertension is to give carrot juice and young coconut water. The aim of this research is to determine the effectiveness of giving carrot juice and young coconut water on changes in blood pressure in hypertension sufferers. This type of research is an experiment with a quasi-experiment design. This research was conducted in Polara Raya in September 2023. The sample was 16 people with hypertension who were given carrot juice and 16 people who were given young coconut water. Blood pressure data was obtained with a sphygmomanometer and analyzed using the Wilcoxon sign rank test and the Mann Whitney test. The research results showed that the average blood pressure before being given carrot juice was 152/97 mmHg and after giving carrot juice it was 142/87 mmHg and the systolic p value was 0.005 and 0.000 in systole. Then the average blood pressure before being given young coconut water was 151/96 mmHg and after being given young coconut water was 144/85 mmHg, the test results obtained a systolic p value of 0.013 and a distolic 0.000. Then for effectiveness, the p value for systole was 0.954 and 0.814 for distole. The conclusion of this study is that carrot juice and young coconut water can reduce blood pressure and there is no difference in the effectiveness of giving carrot juice and young coconut water on changes in blood pressure in hypertensive sufferers.